Indigenous multicultural da'wah in the interfaith Kupatan tradition: An epistemological study - Ahmad Shofi Muhyiddin; Muhammad Qomaruzzaman (Jurnal Ilmu Dakwah, 2026)
Purpose - The purpose of this study is to examine the concept of epistemic integration of indigenous multicultural da'wah and how the tradition of interfaith kupatan serves as a dialectical tool between Islamic ideals and local culture in a multicultural society. This study is based on indigenous Islamic thought, which connects the study of da'wah and multiculturalism with Javanese philosophy and local wisdom practices. Method - The study was carried out using a qualitative philosophical approach, which is based on epistemological perspective through the examination of rituals, symbols, and social relations among different religions. The information was collected by observing rituals, symbols, and social relations among individuals from different religions, and later analyzed to determine their significance. Result  -  The results indicated that the interfaith kupatan tradition reflects the internalization of Islamic principles of raḥmatan li al-‘ālamīn (mercy for all creation) via social practices that promote tolerance, ukhuwah insāniyah (human brotherhood), and social cohesion. From an epistemological perspective, this tradition establishes an adaptive-dialectical-reformative framework for indigenous multicultural da'wah. It combines three sources of understanding: bayānī (religious texts), burhānī (empirical socio-cultural realities), and 'irfānī (empathy, feelings, and spiritual awareness) reasoning, drawing from religious texts and diverse experiences. This approach is proven by achieving harmony, justice, and maqāṣid al-sharī'ah (shared social well-being). Implication – This study confirms the relevance of a qualitative-contextual approach based on field studies in examining multicultural da'wah based on local traditions. These findings imply the need for a dialectical da'wah study methodology oriented towards indigenous knowledge in multicultural societies. Originality/Value - This study's novelty is in proposing a clear and practical model of indigenous multicultural da'wah derived directly from field findings in the interfaith kupatan tradition. This research presents a practical model for integrating Islamic teachings, local culture, and interfaith interaction in daily practice, in contrast to previous studies that are purely theoretical. *** Tujuan - Tujuan penelitian ini adalah untuk mengkaji konsep integrasi epistemologis dakwah multikultural asli serta bagaimana tradisi kupatan antaragama berfungsi sebagai alat dialektis antara cita-cita Islam dan budaya lokal dalam masyarakat multikultural. Penelitian ini didasarkan pada pemikiran Islam asli, yang menghubungkan kajian dakwah dan multikulturalisme dengan filsafat Jawa serta praktik-praktik kearifan lokal. Metode - Penelitian ini dilakukan dengan menggunakan pendekatan filosofis kualitatif, yang didasarkan pada perspektif epistemologis melalui pengkajian ritual, simbol, dan hubungan sosial di antara berbagai agama. Informasi dikumpulkan melalui pengamatan terhadap ritual, simbol, dan hubungan sosial di antara individu dari berbagai agama, kemudian dianalisis untuk menentukan signifikansinya. Hasil  -  Hasil menunjukkan bahwa tradisi kupatan antaragama mencerminkan internalisasi prinsip-prinsip Islam raḥmatan li al-‘ālamīn (rahmat bagi seluruh alam) melalui praktik-praktik sosial yang mempromosikan toleransi, ukhuwah insāniyah (persaudaraan manusia), dan kohesi sosial. Dari perspektif epistemologis, tradisi ini menetapkan kerangka kerja adaptif-dialektis-reformatif untuk dakwah multikultural asli. Tradisi ini menggabungkan tiga sumber pemahaman: bayānī (teks-teks agama), burhānī (kenyataan sosio-budaya empiris), dan 'irfānī (empati, perasaan, dan kesadaran spiritual), yang bersumber dari teks-teks agama dan pengalaman yang beragam. Pendekatan ini terbukti berhasil dalam mewujudkan harmoni, keadilan, dan maqāṣid al-sharī'ah (kesejahteraan sosial bersama). Implikasi – Studi ini menegaskan relevansi pendekatan kualitatif-kontekstual berdasarkan studi lapangan dalam mengkaji dakwah multikultural yang berlandaskan tradisi lokal. Temuan ini mengimplikasikan perlunya metodologi studi dakwah dialektis yang berorientasi pada pengetahuan lokal dalam masyarakat multikultural. Keaslian/Nilai - Keunikan studi ini terletak pada usulan model dakwah multikultural berbasis lokal yang jelas dan praktis, yang langsung dihasilkan dari temuan lapangan dalam tradisi kupatan antaragama. Penelitian ini menyajikan model praktis untuk mengintegrasikan ajaran Islam, budaya lokal, dan interaksi antaragama dalam praktik sehari-hari, berbeda dengan studi sebelumnya yang murni teoretis.